Length Neutrosophic Subalgebras of BCK=BCI-Algebras - Jun, Young Bae; Khan, Madad; Smarandache, Florentin; Song, Seok-Zun (Bulletin of the Section of Logic, 2020)
Given i, j, k ∈ {1,2,3,4}, the notion of (i, j, k)-length neutrosophic subalgebras in BCK=BCI-algebras is introduced, and their properties are investigated. Characterizations of length neutrosophic subalgebras are discussed by using level sets of interval neutrosophic sets. Conditions for level sets of interval neutrosophic sets to be subalgebras are provided.